Handling issues in modified DDGS Bulk transportation of the feedstuff is challenging due to caking, flow problems - Bhadra, Rumela; Ambrose, Kingsly (My University, 2016)
Bulk solids handling in food and biomass processing industries is often associated with handling and transportation problems due to moisture absorption, caking, microbial growth, and overall product quality degradation.
Citation: Bhadra, R. and R. P. Kingsly Ambrose. Handling issues in modified DDGS. World Grain Magazine, April 2014 Issue. Sosland Publishing Co., Kansas City, MO.